Comparison of platform technologies for assaying antibody to Ebola virus. Issue 9 (1st March 2017) - Wilkinson, Dianna E.; Page, Mark; Mattiuzzo, Giada; Hassall, Mark; Dougall, Thomas; Rigsby, Peter; Stone, Lindsay; Minor, Philip
Abstract: Background: The recent Ebola outbreak in West Africa led to the use of a variety of different platform technologies for assaying antibodies because of the difficulties of handling the live virus. The same types of method could be applied rapidly to other infections when they emerge. There is a need to compare quantitative results of different assays, which means that the assays must measure similar parameters and give comparable results. Methods: A collaborative study was carried out to establish an International Reference Reagent through WHO. Nine samples were sent to 16 laboratories and the results from 22 different assays compared to those obtained by neutralisation assays using the wild type virus. Findings: Quantitative correlation with the wild type neutralisation assays was very variable but generally poor, with only five of the twenty-two assays giving a correlation coefficient of 0.7 or greater; the five best assays included methods based on wild type and VSV pseudotype neutralisation and ELISA. They could be applicable to other rapidly emerging diseases. The remaining assays including neutralisation of lentiviral pseudotypes need further development. Interpretation: The assay platform should be chosen with care to ensure that it is fit for purpose. Many of the assays were not suitable for quantitation of antibody levels, a finding that is not surprising given the urgency with which they had to be implemented but some may be of generic value. Antibody titres in samples from a vaccine trial were comparable to those from convalescent patients or lower. Funding: Funding was from the UK DoH and the Wellcome Tust.